Quality and resistance optimization of banana (Musa acuminata L.) vegetative seeds through the addition of indole butyric acid with biological agents induction against fusarium wilt disease intensity - Septia, Erfan Dani; Zakia, Aulia; Zainudinn, Agus; Maftuchah, Maftuchah; Gofur, Abdul; Abbabiel, Yudantara Ekanaradhipa (Universitas Padjadjaran, 2024)
Banana plants are a vital agricultural commodity in Indonesia, but Fusarium wilt disease (Fusarium oxysporum) significantly hampers production. This research aims to improve the quality and resilience of vegetative banana seedlings by selecting superior seedlings and vegetative propagation techniques such as budding, shoot cutting, and tissue culture management. The research used a randomized complete block design (RCBD) factorial with a combination of two factors, namely the addition of IBA and biological agents, with nine treatment combinations and three replications. IBA treatment significantly affected the initial emergence of shoots and leaf area, with the best result from treatment Z2 (IBA concentration of 1.5 g/l). The biological agent factor treatment significantly affected plant height, lower stem diameter, number of leaves, and hypothetical vigor index, with the best value shown by treatment B1. The use of IBA and biological agents can optimize the quality and resilience of vegetative banana seedlings, aiding farmers in enhancing the productivity and quality of agricultural products sustainably.